Competitive strategy : - Porter, Michael E. (Free Press, 1980)
Competitive Strategy is the definitive work on the subject of "competitive strategy," the hottest new concept in American business today. The book addresses major questions of vital concern to managers, and presents a comprehensive set of analytical techniques for understanding a business and the behavior of its competitors